Gender disparities in access to care for time-sensitive conditions during COVID-19 pandemic in Chile - Jorge Pacheco; Francisca Crispi; Tania Alfaro; María Soledad Martínez; Cristóbal Cuadrado (BMC, 2021)
Abstract Background During the COVID-19 pandemic, reductions in healthcare utilization are reported in different contexts. Nevertheless, studies have not explored specifically gender disparities in access to healthcare in the context of COVID-19. Methods To evaluate gender disparities in access to medical in Chile we conducted an interrupted time series analysis using segmented regression. The outcome variable was the number of weekly confirmed cases of a set of oncologic and cardiovascular time-sensitive conditions at a national level. The series contained data from weeks 1 to 39 for 2017 to 2020. The intervention period started at week 12. We selected this period because preventive interventions, such as school closures or teleworking, were implemented at this point. We estimated the level effect using a dummy variable indicating the intervention period and slope effect using a continuous variable from weeks 12 to 39. To test heterogeneity by gender and age group, we conducted a stratified analysis. Results We observed a sizable reduction in access to care with a slowly recovery for oncologic (level effect 0.323; 95% CI 0.291-0.359; slope effect 1.022; 95% CI 1.016-1.028) and cardiovascular diseases (level effect 0.586; 95% CI 0.564-0.609; slope effect 1.009; 95% CI 1.007-1.011). Greater reduction occurred in women compared to men, particularly marked on myocardial infarction (level effect 0.595; 95% CI 0.566-0.627 versus 0.532; 95% CI 0.502-0.564) and colorectal cancer (level effect 0.295; 95% CI 0.248-0.35 versus 0.19; 95% CI 0.159-0.228). Compared to men, a greater absolute reduction was observed in women for oncologic diseases, excluding sex-specific cancer, (1352; 95% CI 743-1961) and cardiovascular diseases (1268; 95% CI 946-1590). Conclusion We confirmed a large drop in new diagnoses for time-sensitive conditions during the COVID-19 pandemic in Chile. This reduction was greater for women. Our findings should alert policy-makers about the urgent need to integrate a gender perspective into the pandemic response.